2010
DOI: 10.1002/jor.21166
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation of secondary bone tumors in vivo: The impact of minor surgery at a distal site

Abstract: Microcirculatory properties of tumors play a pivotal role in tumor progression and inefficacy of therapies. It has been hypothesized that surgical interventions result in an accelerated tumor growth by increasing the level of pro-angiogenic cytokines with subsequent amplification of tumor angiogenesis. To characterize the microvascular properties of secondary bone tumors in vivo and determine the impact of minor surgery on the microcirculation, we performed intravital microscopy over 25 days using a xenograft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
4
10
0
Order By: Relevance
“…Increased engraftment of metastasis [8,16] or accelerated tumor growth has been reported following surgical interventions [17,30]. In our recently published study that was performed under similar conditions to the current study, we reported that minor surgical interventions at a distal site resulted in microvascular alterations and did not change tumor growth kinetics of breast cancer cells in bone [13]. In the aforementioned study, minor surgery resulted in a decrease in the early angiogenic response and microvascular permeability remained constant.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Increased engraftment of metastasis [8,16] or accelerated tumor growth has been reported following surgical interventions [17,30]. In our recently published study that was performed under similar conditions to the current study, we reported that minor surgical interventions at a distal site resulted in microvascular alterations and did not change tumor growth kinetics of breast cancer cells in bone [13]. In the aforementioned study, minor surgery resulted in a decrease in the early angiogenic response and microvascular permeability remained constant.…”
Section: Discussionsupporting
confidence: 85%
“…Increased levels of VEGF result in increased microvascular permeability by loosening intercellular contacts, and decreasing numbers of endothelial cells and increased transcellular openings facilitate the migration of endothelial cells and may lead to pathological extravasation of plasma proteins [31,32]. In the control group, levels of microvascular permeability decreased towards the end of the observation period, corroborating findings from a previous study [13]. The minor surgical intervention did not lead to a significant increase in microvascular permeability; however, in the sunitinib group, a dramatic increase in the level of microvascular permeability was observed on days 8 and 10 following the surgical Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, many new imaging techniques are being developed to detect subtle changes in vascularization as a metric for quantifying the effects of administered therapies (Schaefer et al 2010, Pollard and Larson 2010, Hwang et al 2010). Ultrasound is a popular imaging modality for preclinical and clinical disease characterization alike, as it is portable, safe, and relatively inexpensive.…”
Section: Introductionmentioning
confidence: 99%